Mouse Models of Alzheimer’s Disease - Yokoyama, Miyabishara; Kobayashi, Honoka; Tatsumi, Lisa; Tomita, Taisuke (Frontiers in Molecular Neuroscience, 2022)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by memory loss and personality changes, eventually leading to dementia. The pathological hallmarks of AD are senile plaques and neurofibrillary tangles, which comprise abnormally aggregated β-amyloid peptide (Aβ) and hyperphosphorylated tau protein. To develop preventive, diagnostic, and therapeutic strategies for AD, it is essential to establish animal models that recapitulate the pathophysiological process of AD. In this review, we will summarize the advantages and limitations of various mouse models of AD, including transgenic, knock-in, and injection models based on Aβ and tau. We will also discuss other mouse models based on neuroinflammation because recent genetic studies have suggested that microglia are crucial in the pathogenesis of AD. Although each mouse model has its advantages and disadvantages, further research on AD pathobiology will lead to the establishment of more accurate mouse models, and accelerate the development of innovative therapeutics.